Assessment of urban surface thermal environment using MODIS with a population-weighted method: a case study. Issue 2 (4th May 2019) - Yang, Yuan-Jian; Gao, Zhiqiu; Shi, Tao; Wang, Hong; Li, Yubin; Zhang, Ning; Zhang, Hongqun; Huang, Yong
Abstract: In this paper, taking the Hefei City in China as an example, a population-weighted urban surface thermal environment index (IPWUSTE ) is constructed with the MODIS-based land surface temperature (LST) and the spatial population retrieved from night-time light satellite observations. The results show that the spatial distribution of IPWUSTE corresponds well with the actual distribution of the urban land covers with their surface thermal environments (STEs). Firstly, IPWUSTE can consider and reliably reflect the anthropogenic effects on the urban surface, because spatial IPWUSTE matches well with spatial population and city size. Secondly, IPWUSTE is also useful to understand and reveal the population exposure to high temperature. Thirdly, comparing with the 1-km grid MODIS-based LST, IPWUSTE has a higher resolution of 0.5-km and improves the spatial description of STEs. Over all, IPWUSTE can be effectively applied to reveal the heat exposure of a population and to alleviate heatwave impacts in urban areas in the summer.